Effect of a carbohydrase admixture in growing pigs fed wheat-based diets in thermoneutral and heat stress conditions. (30th August 2021) - Oladele, Paul; Li, Enkai; Lu, Hang; Cozannet, Pierre; Nakatsu, Cindy; Johnson, Timothy; Adeola, Olayiwola; Ajuwon, Kolapo M
Abstract: The efficacy of exogenous carbohydrases in pig diets has been suggested to depend on enzyme activity and dietary fiber composition, but recent evidence suggests other factors such as ambient temperature might be important as well. Therefore, we investigated the effect of heat stress (HS ) on the efficacy of a multienzyme carbohydrase blend in growing pigs. Ninety-six (barrows: gilts; 1:1) growing pigs with initial body weight (BW ) of 20.15 ± 0.18 kg were randomly assigned to six treatments, with eight replicates of two pigs per pen in a 3 × 2 factorial arrangement: three levels of carbohydrase (0, 1X, or 2X) at two environmental temperatures (20 °C or cyclical 28 °C nighttime and 35 °C day time). The 1X dose (50 g/tonne) provided 1, 250 viscosimetry unit (visco-units) endo-β-1, 4-xylanase, 4, 600 units α-l -arabinofuranosidase and 860 visco-units endo-1, 3(4)-β-glucanase per kilogram of feed. Pigs were fed ad libitum for 28 d and 1 pig per pen was sacrificed on day 28. There was no enzyme × temperature interaction on any response criteria; thus, only main effects are reported. Enzyme treatment quadratically increased ( P < 0.05) BW on day 28, average daily gain (ADG ) ( P < 0.05), and average daily feed intake (ADFI ) ( P < 0.05) with the 1X level being highest. HS reduced the BW at day 14 ( P < 0.01) and day 28 ( P < 0.01), ADG ( P < 0.01), and ADFI (P<0.001). There was a trend of increased feed efficiency (G:F ) ( P < 0.1) in the HS pigs. HS increased apparent jejunal digestibility of energy ( P < 0.05) and apparent ileal digestibility of calcium ( P < 0.01). At day 1, HS reduced serum glucose ( P < 0.001) but increased nonesterified fatty acid ( P < 0.01). In the jejunum, there was a trend of increased villi height by carbohydrases ( P < 0.1), whereas HS reduced villi height ( P < 0.05). HS increased the jejunal mRNA abundance of IL1β in the jejunum ( P < 0.001). There was a trend for a reduction in ileal MUC2 ( P < 0.1) and occludin ( P < 0.1) by HS, and a trend for increased PEPT1 ( P < 0.1). There was no effect of HS on alpha diversity and beta diversity of the fecal microbiome, but there was an increase in the abundance of pathogenic bacteria in the HS group. In conclusion, HS did not alter the efficacy of carbohydrases. This suggests that carbohydrases and HS modulate pig performance independently.